2003
DOI: 10.1177/106689690301100402
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of Early Stage (la-Ilb) Uterine Cervical Squamous Carcinoma

Abstract: Cervical cancer is the most common gynecologic malignancy of the developing world. The oncogenic role of human papilloma virus (HPV) is well known. Attention is now focusing on the complicit genetic changes, which allow progression of these tumors. Regarding these changes, deletion of tumor suppressor genes (loss of heterozygosity [LOH]) is the preferred pathway of progression with only a subset manifesting microsatellite instability (MSI). Implicated loci include 3p14.1-22. Several studies suggest that the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(42 reference statements)
1
4
0
3
Order By: Relevance
“…It has been reported that HPV infection compromises the DNA repair system such as alteration in gene amplification, expression of DNA repair enzymes (49) and microsatellite instability (50). It is conceivable that expression and function of genes responsible for the repair of strand breaks might be responsible for the differences in the rate of the repair of CSC-induced damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HPV infection compromises the DNA repair system such as alteration in gene amplification, expression of DNA repair enzymes (49) and microsatellite instability (50). It is conceivable that expression and function of genes responsible for the repair of strand breaks might be responsible for the differences in the rate of the repair of CSC-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…SSBs represent the initial DNA damage and are often used as a biomarker of exposure (22)(23)(24). DSBs are considered to be more biologically relevant since they can lead to chromosome INTERNATIONAL JOURNAL OF ONCOLOGY 35: 1297-1304, 2009 Cigarette smoke-induced DNA damage and repair detected by the comet assay in HPV-transformed cervical cells translocation and cancer if repaired improperly in addition to genetic instability and cell death if left unrepaired (25). Cellular DNA repair capacity is of particular importance since it is a primary factor in how well a cell can overcome DNA insults by a genotoxic agent.…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, los estudios sobre CaCu y HPV están focalizados sobre las alteraciones genéticas que generan una mayor susceptibilidad para que la célula hospedera sufra transformación maligna 4,5,30 . Entre ellas, se encuentran la deleción alélica (LOH) relacionada con inactivación de genes supresores de tumores y que ha sido descrita en la progresión de lesiones preneoplási-cas.…”
Section: Discussionunclassified
“…Sin embargo, la infección por sí misma, es insuficiente para la transformación del epitelio cervical, sugiriendo que otros factores como, la pérdida de la heterocigosidad (LOH) o la inestabilidad de microsatélites (MSI), podrían estar involucrados en la tumorigénesis cervical [3][4][5] .…”
unclassified
“…It has been reported that HPV infection compromises the DNA repair system such as alteration in gene amplification, expression of DNA repair enzymes [146] and microsatellite instability [147]. It is conceivable that expression and function of genes responsible for the repair of strand breaks might be responsible for the differences in the rate of the repair of CSC-induced damage.…”
Section: E Discussionmentioning
confidence: 99%